Sex in College Relationships: The Role Television Plays in Emerging Adults' Sexual Expectations in Relationships. Issue 1 (2nd January 2016) - Gamble, Hilary; Nelson, Leslie R.
Abstract : The purpose of this study was to determine whether emerging adults use relationship television to form their expectations for sexual interaction in romantic relationships. Considering emerging adulthood is a unique period of development providing opportunities to experiment with adult identities, and relationship television contains multiple consistent messages about gender roles in sexual relationships, we questioned whether emerging adults' relationship television viewing may be related to their sexual expectations in relationships. Our findings indicated women's relationship television viewing was associated with expecting more sexual interaction in their relationship. Men's sexual expectations were moderated by perceived realism. Men who watched more relationship television, and perceived that television to be less realistic, reported expecting less frequent sexual interaction.